An unusual finding after surgical treatment of corrosive oesophageal stricture - Pazhanivel Mohan; Santhosh Anand (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Mohan P, Anand S. An unusual finding after surgical treatment of corrosive oesophageal stricture. Turk J Gastroenterol 2019; 30: 109-10.